Effects of Subcutaneous Injection in Mice with Oral Prevotella intermedia Clinical Isolates in Malaysia - Himratul-Aznita, W.H.; Ali, T.B.T.; Sushil, K.; Zainuddin, S.L.A.; Mahmood, A.A.; Ansary, A. (Asian Network for Scientific Information, 2005)
The study was undertaken with the aims of identifying strains providing virulent toxin and to observe the histological effect of the toxin in mice. Plaque samples were collected from adult periodontitis patients. P. intermedia were recovered from subgingival periodontal pocket with depths of 5 mm or greater. Ninety P. intermedia isolates were identified based on its bacteriological properties, gram staining and biochemical characteristics. The clinical isolates of P. intermedia were assessed for their potential and ability to produce toxin and form skin lesion in balb/c mice. 108, 1010 and 1012 cells mL 1 of bacterial suspension were used in the study. No lesion was observed in mice injected with 108 cells mL 1 and only three P. intermedia with concentration 1010 cells mL 1 were able to induce localized skin lesion in balb/c mice. However, all isolates causes balb/c mice to develop localized skin lesion when 1012 cells mL 1 was used. Infected mice appeared cachectic and the histological effect of the skin lesion showed that all lesions were localised at the injection site and causes tissue damage with skin necrosis and hair loss.